KOMUNIKASI INSTRUKSIONAL GURU DALAM PROSES BELAJAR MENGAJAR BIDANG TATA KECANTIKAN KULIT DI SMK NEGERI 3 PEKANBARU - Sakinah "; Nova Yohana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Vocational high school or called SMK with a variety of majors such as culinary, clothing, multimedia, machinery, not only that SMK also presents majors beauty. Different from time immemorial education that usually only provide formal subjects to students but now education also strives to provide expertise and creativity to students so that students are able to use these skills to become an independent society. The purpose of research thatb is 1. Know the credibility of teacher instruction communicator in the process of learning to teach the field of skin beuty in smk n 3 pekanbaru. 2. Knowing the instructional communication media of teacher in teacing in learning process in the field of skin beuty in smk n 3 pekanbaru. 3. Knowing the instructional communication method of teachers in the learning process teaching the field of skin beuty in smk n 3 pekanbaru. 4. Konowing the barriers of instructional communication of teachers in teaching and learning process the field of skin beuty in smk n 3 pekanbaru.This research uses qualitative research with descriptive approach. Research subjects consisted of 5 skin beauty teachers and 10 students using Purposive technique, that is based on predetermined criteria. Data collection techniques in this study with interviews, observation, and documentation. The technique of data validity in this study is extension of participation and triangulationThe results showed that the credibility of communicators can be seen from the expertise and belief. Competent, teachers must have a professional license certificate, have sufficient expertise and knowledge, experience and trained. In addition, trust that looks sincere in leading the activities, has the trust of the students, must be honest and moral well and have extensive knowledge. The instructional communication method used is the lecture method, explaining to the students about the lesson objectives and the issues that will be discussed. methods of assigning tasks, methods of presentation and demonstration discussions. Instructional communication media used is the media syllabus, RPP, textbooks beauty, laptop, infokus and cosmetic tools. Obstacles that exist in the learning process that is the psychological barriers and technical barriers, which comes from self, the lack of attention of students to the lessons, as well as interference friends. Technical barriers to lack of focus, lack of lessons and less effective class conditions.Key Word:Instructional communication, skin beuty, and teacher in learning